A Study of the Christian Leprosarium in Teng County, Shandong - WANG Delong, (Journal of Research for Christianity in China (JRCC), 2025)
The Tengxian Leprosarium was a religious charity founded by American missionary Mary D. Moore. Its early funding primarily came from donations by the International Leprosy Relief Association, while during the War of Resistance Against Japan, it relied on fundraising by local Chinese church members. The institution primarily focused on sheltering patients, yet also achieved significant success in isolation treatment. Beyond medical care and occupational therapy, its religious-based spiritual therapy proved highly valuable. It offered despairing leprosy patients hope for life and communal care, embodying the humanitarian concern of medical charities that emphasize both physical and spiritual well-being.